Mechanism of antibacterial action of the alcoholic extracts of Hemidesmus indicus (L.) R. Br. ex Schult, Leucas aspera (Wild.), Plumbago zeylanica L., and Tridax procumbens (L.) R. Br. ex Schult - Saritha, Kongari; Rajesh, Angireddy; Manjulatha, Khanapur; Setty, Oruganti H.; Yenugu, Suresh (Frontiers in Microbiology, 2015)
Herbal products derived from Hemidesmus indicus (L.) R. Br. ex Schult, Leucas aspera (Wild.), Plumbago zeylanica L and Tridax procumbens (L.) R. Br. ex Schult. are widely used in traditional medicine.Though the extracts of these plants were found to be antimicrobial in nature and have the potential to be used in clinics, the mechanism of action of is not reported. The ethanolic extracts of Hemidesmus indicus (L.) R. Br. ex Schult (HIEE), Leucas aspera (Wild.)(Wild.)(LAEE), Plumbago zeylanica L (PZEE) and Tridax procumbens (L.) R. Br. ex Schult. (TPEE) were tested for their antibacterial activity against E. coli. Antibacterial activity was analyzed by CFU assay and the effect on the bacterial membrane by fluorescence activated cell sorting and scanning electron microscopy. LAEE, PZEE and HIEE displayed potent bacterial killing activity in a time and concentration dependent manner. TPEE did not display appreciable antibacterial activity. The antibacterial action involved disruption of membrane potential, inner membrane permeabilization , blebbing and leakage of cellular contents. Our results contribute to the understanding of the antibacterial mechanism of alcoholic extracts of the medicinal plants used in this study.